Nickel-containing alloys in hydrofluoric acid, hydrogen fluoride, and fluorine - Schillmoller, C. M. (Technical series (Nickel Development Institute (Canada)) ;, 2020)
This publication is intended to illustrate some of the corrosion experiences involved in handling hydrofluoric acid (HF) and anhydrous hydrogen fluoride (AHF) as well as the handling of fluorine. AHF contains a maximum of 400 ppm H2O; HF includes all water solutions of hydrogen fluoride, which, at normal atmospheric pressure, are limited to a maximum of about 80% hydrogen fluoride.